Síntese e caracterização de novos complexos supramoleculares derivados do ferroceno e do ligante fenilenobis(oxamato) - Ana Luísa Almeida Lage (2015)
In this work, the synthesis and characterization of five new compounds are described, being two of them complexes containing ferrocene and other three are supramolecular complexes containing two derivatives of the building block [Cu(opba)]2- (opba = ortho-phenylenebis(oxamate)): (Bu4N)2[Cu(dmopba)] (dm = dimethyl) and (Bu4N)2[Cu(dcopba)] (dc = dichloro). The counterion for these complexes is tetrabuthylammonium (Bu4N+). To the formation of imines with ferrocene compounds, a condensation reaction using two different synthetic routeswas done: first of all, using ortho-phenylenediamine and benzene as a solvent, resulting in the compound [1-{N-2-(phenylamine)ferrocene}iminemethyl] (1). Secondof all, using hydroxylamine chlorohydrate and dry methanol as a solvent, forming acetylferroceneoximine(oxamate). For compound 1 it was possible to obtain single crystals for X-ray diffraction crystallography. To compounds 1 and 2 electrochemical studies showed a small influence of the substituents on the redox potentials of iron if compared to the ferrocene free. For compounds (Bu4N)2[Cu(dmopba)] and(Bu4N)2[Cu(dcopba)] it has been used the strategy complex as ligand for synthesis of three new supramolecular compounds using the building block bis(2-pyridylcarbonyl)amidate copper(II), [Cu(bpca)(H2O)2]NO3.2H2O: a hexanuclear compound {[Cu(bpca)]2[Cu(dmopba)(H2O)]}2·4H2O (compound 3) and two trinucleaires {[Cu(bpca)]2[Cu(dcopba)(dmso)} (compound 4) and{[Cu(bpca)(H2O)][Cu(bpca)][Cu(dcopba)(dmso)} (compound 5). For compound 3, magnetic studies showed an antiferromagnetic coupling (J) of -69.8 cm-1. For this compound, the saturation of the magnetization at 2 K was not reached to the maximum of applied field of 50 kOe. Compounds 4 and 5 were obtained in the same synthesis process and they have basically the same crystal structure. The differenceconsists in the presence of one water molecule in 5.